Powder injection moulding, its outstanding features an development - Jamaluddin, Khairur Rijal (Penerbit UTM, 2008)
Metal Injection moulding (MIM) is a development of the traditional powder metallurgy (PM) process and is rightly regarded as a branch of that technology. Th e standard PM process is to compact a lubricated powder mix in a rigid die by uniaxial pressure, eject the compact from the die, and sinter it. It is a novel process which combines the plastic injection moulding with the conventional powder metallurgy technology. Quite complicated shapes can be and are regularly being produced by the million, but there is one significant limitation as regards to shape. In the MIM process, there are four processing steps: (1) mixing – compounding the metal powder and organic binder into feedstock; (2) moulding – shaping the parts from feedstock as in plastic inject ion moulding; (3) debinding – removing the binder in the moulded parts by pyrolysis or solvent soaking; (4) sintering –densifyi ng the debound parts to a high final density.